2021
DOI: 10.13052/jmm1550-4646.1816
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm-Conditional Mutual Information Maximization based feature selection for Bot Attack Classification in IoT devices

Abstract: The evolution of computing is increasing in a vast manner that will integrate many physical objects and the internet to generate a new interconnection, such as the Internet of Things (IoT). It is estimated that the number of devices that will be interconnected to the internet will be more than trillions until 2025. Due to the lack of interoperability when these devices are interconnected in a vast heterogeneous network, it is tough to define and apply security mechanisms. The IoT networks have been exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This method measures the dependence between each feature and the class label and selects the features with the highest mutual information scores [ 44 ]. The main advantage of using mutual information is that it considers the nonlinear relationships between features and class labels, making it suitable for handling complex and nonlinear data patterns in IoT environments [ 48 , 49 ]. Furthermore, mutual information is also able to handle noisy and incomplete data, which are commonly encountered in IoT networks [ 48 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method measures the dependence between each feature and the class label and selects the features with the highest mutual information scores [ 44 ]. The main advantage of using mutual information is that it considers the nonlinear relationships between features and class labels, making it suitable for handling complex and nonlinear data patterns in IoT environments [ 48 , 49 ]. Furthermore, mutual information is also able to handle noisy and incomplete data, which are commonly encountered in IoT networks [ 48 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…By selecting the most relevant and informative features, mutual information feature selection can effectively reduce the dimensionality of the data and improve the accuracy of the IDS. Several studies have demonstrated the effectiveness of mutual information feature selection for IDS in IoT environments and have compared its performance with other feature selection methods [ 45 , 49 , 51 ].…”
Section: Introductionmentioning
confidence: 99%